HUMAN SECURITY FOR BORDER SOCIETY: A CASE STUDY AT WARIS COMMUNITY AT THE BORDERS OF RI-PNG - Melyana Ratana Pugu; Yanyan Mochamad Yani (Kajian Asia Pasifik, 2019)
This research is aimed to explain the border society situation at Waris District, which is located remote from government services. This condition reflects a threat on human security at the borders in Keerom regency, Papua, which is directly bordering Papua New Guinea (PNG). This research uses qualitative research method, in which it explains the human security threat in education and health at Waris District, which borders PNG. The education and health improvement and development for Waris community are organized through the provision infrastructure such as: the number of schools, teachers, community health centres. These are the indicators for the education and health improvement and development in the border region. The outcome of this research is a reference for the government in border region management in the sectors of education and health, as an effort to minimise human security threat for the Waris community at the borders between RI-PNG. Keywords: Human Security, Border Society, Waris, Indonesia, Papua New Guinea Abstrak Penelitian ini bertujuan untuk menjelaskan situasi masyarakat perbatasan di Distrik Waris yang berlokasi terpencil jauh dari pelayanan publik dari pemerintah. Kondisi ini menyebabkan adanya ancaman terhadap keamanan manusia di daerah perbatasan Kabupaten Keerom, Papua yang langsung berbatasan dengan Papua Nugini. Penelitian ini menggunakan metode penelitian kualitatif untuk menjelaskan ancaman terhadap keamanan manusia di bidang pendidikan dan kesehatan di Distrik Waris yang berbatasan langsung dengan Papua Nugini. Pembangunan dan peningkatan bidang pendidikan dan kesehatan dilakukan melalui pengadaan infrastruktur seperti jumlah sekolah, guru, pusat-pusat kesehatan masyarakat. Ini semua merupakan indikator untuk pembangunan dan peningkatan bidang pendidikan dan kesehatan di kawasan perbatasan. Hasil penelitian menjadi bahan masukan bagi pemerintah dalam mengelola kawasan perbatasan terutama di sector pendidikan dan kesehatan, sebagai upaya untuk meminimalkan ancaman terhadap keamanan manusia di Distrik Waris yang berada di daerah perbatasan antara Republik Indonesia dan Papua Nugini. Kata Kunci: Keamanan Manusia, Masyarakat Perbatasan, Waris, Indonesia, Papua Nugini